Solar-powered Hydrogen Refueling Stations: A techno-economic analysis - Micena, Raul Pereira [UNESP]; Llerena-Pizarro, Omar R. [UNESP]; de Souza, Teófilo Miguel [UNESP]; Silveira, José Luz [UNESP] (Elsevier, 2019)
Fuel cell vehicles are a possible alternative for allowing a replacement of fossil-fuel based transportation. Thereby, this work's methodology proposes a Hydrogen Refueling Station (HRS) design powered by a photovoltaic plant for supplying the taxi fleet in a Brazilian city considering different scenarios and assuming that hydrogen-powered vehicles replace the current fleet. Results show that in order to supply 100% of the taxi fleet with hydrogen, 185.4 kgH2/day are necessary, while only 19.8 kgH2/day are enough to supply just 10% of it. Results also reveal slight variations in energy intensity. Hydrogen production costs are inversely proportional to the HRS's production capacity. Hydrogen costs about US$ 8.96/kg for larger HRSs and US$ 13.55/kg for smaller ones. Finally, the proposed system is an attractive alternative in the future nationwide, due to the fact that the cost of electricity has been escalating year after year above inflation rates.
Keywords: Electrolysis; Fuel cell vehicles; Hydrogen refueling station; Solar photovoltaic power; Technical-economic analysis